Concurrent Effects of Exercise and Curcumin on Spatial Learning and Memory in Sensitized Male Mice Following Morphine Administration: - Elhampour, Laleh; Azarbayjani, Mohammad Ali; Nasehi, Mohammad; Peeri, Maghsoud (Galen Medical Journal, 2019)
Background: Exercise and Curcumin have positive effects on spatial memory and cognition independently. The present study aims to investigate whether the combination of ineffectual dosage of these factors can affect cognition and as a solvent if DMSO is involved in Curcumin effects. Materials and Methods: Male NMRI mice (1-month-old) swam (1 week) for 60 minutes (5days/week) and injected with morphine (2.5 mg/ml/kg, intraperitoneal) for five days. Spatial learning and memory were assessed by Moris Water Maze test on the 10th day after stopping morphine injection. Results: The findings revealed that exercise, dimethyl sulfoxide (DMSO), and Curcumin increased memory formation induced by 2.5 mg/ml/kg morphine. DMSO+exercise decreased memory formation induced by morphine, but curcumin +exercise could return the effect of DMSO on the cognition. Conclusion: As a solvent, DMSO had independent effects on memory, which lead to memory impairment in combination with exercise. Therefore, considering its unpredictable effects on cognitive performance, it should be replaced with another solvent or might be used carefully in behavioral experiments. [GMJ.2019;8:e1072]